Expression and differentiation between OCT4A and its Pseudogenes in human ESCs and differentiated adult somatic cells. - Mojca Jez; Sakthikumar Ambady; Olga Kashpur; Alexandra Grella; Christopher Malcuit; Lucy Vilner; Primoz Rozman; Tanja Dominko (PLoS ONE, 2014)
The POU5F1 gene codes for the OCT4 transcription factor, which is one of the key regulators of pluripotency. Its transcription, alternative splicing, and alternative translation leading to the synthesis of the active, nuclear localized OCT4A has been described in detail. Much less, however, is known about actively transcribed OCT4 pseudogenes, several of which display high homology to OCT4A and can be expressed and translated into proteins. Using RT-PCR followed by pseudogene-specific restriction digestion, cloning, and sequencing we discriminate between OCT4A and transcripts for pseudogenes 1, 3 and 4. We show that expression of OCT4 and its pseudogenes follows a developmentally-regulated pattern in differentiating hESCs, indicating a tight regulatory relationship between them. We further demonstrate that differentiated human cells from a variety of tissues express exclusively pseudogenes. Expression of OCT4A can, however be triggered in adult differentiated cells by oxygen and FGF2-dependent mechanisms.